Evaluasi Waktu Tunggu Pelayanan Resep Apotek X Kota Bukittinggi - Ainun Naim; Muhajri Agusfina; Renatalia Fika; Budi Setiawan; Afifah Dwi Asti (Journal Pharma Saintika, 2024)
A pharmacy is a pharmaceutical service facility where pharmaceutical practice is carried out by pharmacists. Waiting time for prescription services has an important role in health services. The waiting time is set by the Republic of Indonesia Minister of Health Regulation No. 73 of 2016, which is between 15-30 minutes. This study aims to determine the average waiting time for prescription services at the XPharmacy, Bukittinggi City. The research method used is a quantitative descriptive method and concurrent data collection, that is, research is carried out simultaneously with the services being carried out. The sampling technique used simple random sampling technique and the research was conducted for 2 months. From a total sample of 353 recipes, 231 concocted recipes and 122 non-concocted recipes were obtained. The research results obtained were that the average waiting time for services for concocted prescriptions was 11.23 minutes and for non-concocted prescriptions was 6.13 minutes. The conclusion of this research is that the average waiting time for prescription services at the XPharmacy for compounded and non-concocted medicines is in accordance with the standards set by the Republic of Indonesia Minister of Health Regulation No. 73 of 2016 concerning Pharmaceutical Service Standards in Pharmacies.